Design Job Vacancy Website Using The Laravel Framework - Moch Farid Fauzi; Govin Yudian Pradipta; Deny Setiyawan; Muhammad Nur Ichsan; Dzaki Ahsana Reyhandhipa (Mobile and Forensics, 2024)
Job vacancies are the most sought after during the current COVID-19 pandemic—the number of layoffs by companies experiencing problems in their business. Many people become unemployed, and income levels decrease while their needs must still be met. This has an impact on the number of people looking for job vacancies. Often found job seekers and job seekers seeking information still through mass media, banners, posters, billboards, and word of mouth. This search and recruitment model will not be efficient and will not be right on target. The solution offered to overcome these problems is to create a website for job vacancies, recruitment, and job applications. The research method used is Rapid Application Development (RAD) to find out the website creation process carried out in a short and influential period. The research flow is looking for references, determining project needs by making UI design and database design, making prototypes, testing, refining, developing features, feedback questionnaires, and project implementation. This research resulted in a job vacancy website called "AntiNggur". This website is expected to facilitate the dissemination of information on job vacancies, the job search process, and the process of recruiting new workers that are more effective and more targeted.